Community Behaviour in Efforts to Prevent Covid-19 Transmission in The City of Padang - Wirna Putri, Novia; Pristi Rahmah, Septia (KnE Life Sciences, 2021)
During the Covid-19 pandemic, people are asked to stay at home to break the chain of disease transmission. The purpose of this study was to see an overview of the people’s attitude towards Covid-19 prevention measures in the city of Padang. This descriptive analytic study was carried out in 2020 in the city of Padang. The study included 401 individuals who responded to the google form questionnaire. Data analysis includes univariate analysis. The results showed that community behaviour in efforts to preventing the transmission of Covid-19 was categorized as bad by 48.6% and good by 51.4%. Some community behaviours that are still poor include the habit of shaking hands with other people by 50.9%, being in a crowd when out of the house by 41.6%, and participating in joint activities by 62.6%. The most important strategy at this time for the people is to wash hands and use hand sanitizer every time they interact with others and reduce the interactions with people outside home. For the government, tightening quarantine rules for areas that are still in the red zone of Covid-19 transmission is important. Keywords: Covid-19, community behaviours, prevention